Bismuth ferrite reinforced porous bioactive glass scaffolds: In vitro and antibacterial properties - S. Amitha Banu; Sk Hasanur Rahaman; Khan Sharun; Merlin Mamachan; Swapan Kumar Maiti; Amarpal; Subhadip Bodhak; Vamsi Krishna Balla; Abhijit M. Pawde (Heliyon)
Tissue engineering focuses on restoring damaged tissues by strategically integrating cells, bioactive factors, and scaffold materials. Despite significant advancements in biomaterials, developing an ideal scaffold for bone regeneration remains a major challenge. The porous scaffolds aim to provide a structural framework that mimics the extracellular matrix, facilitating cellular attachment, proliferation, and differentiation. In this study, we synthesized bismuth ferrite (BF)-incorporated bioactive glass (BAG) composites (0.5–1.5 wt% BF) to investigate their potential in bone tissue engineering (BTE) applications. BF, a multiferroic material, was integrated into the composite to generate in-situ electrical stimuli, mimicking the piezoelectric nature of natural bone and thus promoting early-stage osteogenesis. The MC3T3-E1 pre-osteoblast cells were seeded onto the composites, which exhibited excellent biocompatibility and cell proliferation, as confirmed by live/dead and MTT assays. These porous scaffolds, made using the foam replication method, were characterised for their physical, chemical, and mechanical properties, followed by bioactivity and antibacterial assessments. The BAG and BAG-BF porous scaffolds exhibited porosities of ∼74 % (BAG), ∼65 % (0.5 BAG-BF), and ∼64 % (1.5 BAG-BF), with post-sintering weight losses of 5 %, 2.5 %, and 5 %, respectively. All samples showed ∼50 % shrinkage. The incorporation of bismuth ferrite enhanced the compressive strength, with 0.5 BAG-BF (1.81 MPa, ∼29 % increase) and 1.5 BAG-BF (1.87 MPa, ∼33 % increase) compared to pure BAG (1.45 MPa). These results highlight the potential of BAG-BF composite scaffolds for improved mechanical performance in BTE applications. The cell proliferation assay demonstrated enhanced cell proliferation in dense BAG-BF samples. The 0.5 BAG-BF group exhibited ∼130 % proliferation (0 mT) and ∼170 % (200 mT) by day 5, while the 1.5 BAG-BF group showed ∼140 % (0 mT) by day 7 and ∼185 % (200 mT) by day 5. These results indicate the positive influence of BF and the magnetic field on cell growth. Our findings demonstrate that BAG-BF scaffolds provide a favourable environment with enhanced bioactivity, cell proliferation, and antibacterial activity, highlighting their potential in BTE. Incorporating BF enhances the scaffold's structural and biological properties and introduces a novel approach to harnessing electrical stimulation for bone regeneration.